Rocky IV - Chartoff, Robert; Winkler, Irwin; Stallone, Sylvester; Shire, Talia; Young, Burt.; Weathers, Carl.; Nielsen, Brigitte; Lundgren, Dolph, 1959-; DiCola, Vince; Metro-Goldwyn-Mayer.; United Artists Corporation; MGM Home Entertainment Inc. (Santa Monica, CA : MGM Home Entertainment, 2004)
Rocky's training regimen takes him to icy Siberia, where he prepares for a globally televised match against a vicious Soviet fighter, Drago, who literally killed his last opponent.
DVD, full screen presentation on one side, widescreen presentation on other side; 5.1 surround, mono.
Soundtrack in English or French with optional subtitles in English, French and Spanish; closed-captioned for the hearing impaired.
Sylvester Stallone, Talia Shire, Burt Young, Carl Weathers, Brigitte Nielson, Dolph Lundgren.
Director of photography, Bill Butler ; editors, Don Zimmerman, John W. Wheeler ; music, Vince DiCola.
Originally released as a motion picture in 1985.
"Rocky anthology"--Set container.
Keywords: Boxing -- Training; Boxers (Sports) -- Drama; Siberia (Russia) -- Drama; Boxeo -- Adiestramiento -- Teatro; Boxeadores -- Teatro; Siberia (Rusia) -- Teatro; Boxing -- Training; Boxers (Sports) -- Drama; Siberia (Russia) -- Drama; Boxers (Sports); Boxing -- Training; Russia (Federation) -- Siberia; Feature films; Video recordings for the hearing impaired; Drama